2009
DOI: 10.1111/j.1365-2559.2009.03399.x
|View full text |Cite
|
Sign up to set email alerts
|

Histogenesis‐specific expression of fibroblast activation protein and dipeptidylpeptidase‐IV in human bone and soft tissue tumours

Abstract: Aims:Fibroblast activation protein (FAP)/seprase and dipeptidylpeptidase-IV (DPP-IV)/CD26 are serine integral membrane proteases. They are involved in tissue remodelling, cancer invasion and metastases, mechanisms that are controversial. The aim was to identify cell types that express FAP and DPP-IV in human bone and soft tissue tumours, and to determine whether there are any correlations between the expression of FAP and DPP-IV and the malignant potential of tumours.Methods and results:This study analysed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 20 publications
4
76
0
1
Order By: Relevance
“…FAP has been shown to be expressed by synovial fibroblasts in both RA and OA patients [40]. Its expression has also been demonstrated in several bone tumors including low-grade myofibroblastic sarcoma and osteosarcomas [41]. In this study, it was found to be upregulated in OA synovial fluid by 5-fold.…”
Section: Resultssupporting
confidence: 53%
“…FAP has been shown to be expressed by synovial fibroblasts in both RA and OA patients [40]. Its expression has also been demonstrated in several bone tumors including low-grade myofibroblastic sarcoma and osteosarcomas [41]. In this study, it was found to be upregulated in OA synovial fluid by 5-fold.…”
Section: Resultssupporting
confidence: 53%
“…21 As to bone and soft tissue sarcomas, expression of FAP is clearly independent of the malignant potential of the tumor, and is rather related to the histogenesis of the tumor cells. 22 Based on the highly regulated expression and restricted distribution of FAP, it has been identified as a marker of reactive tumor stromal fibroblasts. Ossama Abbas et al 23 reported the differentiation of morpheaform/infiltrative basal cell carcinoma from desmoplastic trichoepithelioma using FAP as a marker.…”
Section: Tissue Distribution Of Fapmentioning
confidence: 99%
“…A hallmark of these activated fibroblasts is the expression of fibroblast activation protein alpha (FAP) [4,5]. This molecule is most prominently expressed on CAFs, but its surface expression has also been detected in bone and soft tissue sarcomas and in malignant melanomas [6,7]. It is a homodimeric type II transmembrane serine protease with postprolyl cleavage specificity and harbors both dipeptidase and endopeptidase activity [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%